PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI DI PT. POLYPLEX FILMS INDONESIA - Fatari Fatari; Seno Firmansyah (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
This study aims to determine how much influence the work environment and motivation have on the performance of employees in the production department at the manufacturing company PT. Polyplex Films Indonesia. This research uses descriptive quantitative method with correlational analysis. The size of the population and the sample are 58 employees of the production division, using a saturated sample, namely all existing employees. The results of testing the T hypothesis, the work environment has no effect on employee performance, obtained a T value (Tcount 1.657 < Ttable 2.00404), hypothesis 2 that motivation has a positive effect on employee performance obtained the t-value (t count 2.787 > t table 2.00404). Simultaneously the work environment and motivation on employee performance is shown by the value of Fcount of 14.511 > Ftable 3.16. Partially the work environment has no effect on employee performance, but simultaneously the work environment and motivation affect employee performance with a contribution of 34.5%